Hybrid Model for Improving the Accuracy of Software Development Team Effort Estimation with Genetic Algorithm-Optimized Regression Ensembles - Silva, Wilamis Kleiton Nunes da (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE); 2026: Anais do XXIX Congresso Ibero-Americano em Engenharia de SoftwareDO - 10.5753/cibse.2026.42458, 2026)
This thesis plan aims to propose a Hybrid Model for Software Development Team Effort estimation by integrating Regression Ensembles and GA. The methodology will consist of an experimental evaluation of the proposed machine learning model using multiple datasets from the PROMISE repository, employing the evaluation metrics MAE, RMSE, MdMRE, PRED(25), and R2 score to analyze predictive performance.